IMPACT OF CIVIC EDUCATION ON COMMUNITY-LED CRIME CONTROL MODEL IN FCT-ABUJA, NIGERIA - Sule Omeiza Adebayo; Blessing Ikechi Onyedum; Chukwuma Victoria Azuka; Emmanuel Lucas Nwachukwu (CV. Tirta Pustaka Press, 2026)
Crime and insecurity, particularly rising incidents of urban theft, kidnapping, and organized street crime, remain critical challenges in Nigeria's Federal Capital Territory (FCT-Abuja), necessitating innovative community-based approaches to complement conventional policing strategies.. This study examined the impact of civic education on community-led crime control participation in FCT-Abuja. A quantitative survey design was employed involving 400 adult residents selected through proportionate stratified random sampling across six Area Councils, with validated structured questionnaires ensuring reliability and representativeness of the data. Data were collected using a structured questionnaire with dichotomous (Yes/No) items operationalizing key variables, including levels of civic education exposure and forms of community crime control participation. Chi-square test of independence analyzed the relationship between variables at 0.05 significance level. Findings revealed that 69.6% of respondents had been exposed to civic education programs, while 65.2% participated in community crime control activities. Chi-square analysis (χ² = 56.842, p < 0.001) revealed a statistically significant association between civic education exposure and community crime control participation. Residents exposed to civic education were nearly twice as likely to participate in crime control activities (76.5%) compared to unexposed residents (39.3%), representing a 37.2 percentage point difference. Civic education significantly enhances community-led crime control participation in FCT-Abuja. Policymakers should prioritize targeted expansion of civic education programs in underserved communities, integrate digital and community-based delivery platforms, and institutionalize continuous engagement frameworks to sustainably strengthen community security capacity across all Area Councils.